Efficacy and safety of the new TightRail™ mechanical sheath for transvenous lead extraction: Results of a French multicenter study. (11th February 2022) - Artus, Adrien; Mansourati, Jacques; Fatemi, Marjaneh; Pierre, Bertrand; Schatz, Alexandre; Badoz, Marc; Laurent, Gabriel; Guenancia, Charles; Garnier, Fabien
Abstract: Introduction: The aim of this study was to assess the safety and efficacy of the TightRail™ sheath for pacemaker/defibrillator transvenous lead extraction (TLE). Methods: Multicenter observational study including patients who underwent a TLE with the TightRail™ sheath in five French university hospitals from September 2014 to January 2020. Results: Two hundred and twenty‐five patients (76% males, 71 ± 12 years) underwent a TLE procedure with the TightRail™. A total of 438 leads were extracted using the TightRail™, and the mean age of the extracted leads was 128 ± 85 months; of these, 344 (79%) were pacing leads and 94 (21%) were implantable cardioverter defibrillator leads. The overall clinical success of the extraction procedures was 93%. Overall, 410 of the 438 leads (95%) were extracted (complete or incomplete removal). After multilevel mixed‐effects logistic regression model, we found that lead age (odds ratio [OR], 95% confidence interval [CI] for a 1 year increase: 1.11 [1.07–1.15], p < .001) and number of leads extracted (OR, 95% CI: 2.09 [1.50–2.96], p < .001) were the two independent factors associated with complete lead removal failure. Finally, there were 7 (3%) cases of major complications but no per‐procedural death. Conclusion: This is the first large‐scale survey assessing the efficacy and safety profile of the Tightrail™ mechanical sheath. The clinical success rate was 93%, and the lead removal failure was dependent on the age and number of leads. We show a satisfactory safety profile in this cohort of patients from primarily low‐volume centers with older leads.